Iñupiaq pride: Kivgiq (Messenger Feast) on the Alaskan North Slope - Ikuta, Hiroko (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThis paper explores tradition as dynamics of social life, history, and power relations and its meanings for local people through the examination of a revitalised ancient festival among Iñupiat on the Alaskan North Slope. In one form or another, Iñupiaq people had celebrated Kivgiq (Messenger Feast) for many centuries. However, the earlier representations of Kivgiq were discontinued in the early 20th century due to social, economic, and environmental pressures. In 1988 after a lapse of more than 70 years, the modern Kivgiq was reconstructed with intent to provide each Iñupiaq with an even stronger collective identity and enhanced ethnic pride. The first modern Kivgiq generated more than 2,000 participants and successfully integrated ancient values into those of the modern context. Now held every second year, the revitalised tradition embodies Iñupiaq socio-economic empowerment. Kivgiq is one of the most important activities to index what contemporary Iñupiat mean by tradition. Along with many other traditional activities defined by Iñupiat, such as whaling, hunting, and dancing, the contemporary Messenger Feast is the key sphere where people regenerate, reinterpret, and renegotiate their traditions to themselves and to wider audiences.